2011
DOI: 10.5194/acp-11-2031-2011
|View full text |Cite
|
Sign up to set email alerts
|

Charge induced stability of water droplets in subsaturated environment

Abstract: Abstract. Atmospheric liquid and solid water particles are stabilized if they are coated with either negative or positive electric charge. The surface charge causes an increase of the partial pressure of water vapour close to the surface of each particle, effectively allowing the particles to remain in their condensed phase even if the environmental relative humidity drops below unity. The theory, briefly presented in this paper, predicts a zero parameter relation between surface charge density and water vapou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Nielsen et al . 69 have recently shown size–charge association for the case of a charged, micron-size pure water droplet. It was demonstrated that the surface charge effectively increases surface tension leading to a reduced evaporation rate.…”
Section: Resultsmentioning
confidence: 99%
“…Nielsen et al . 69 have recently shown size–charge association for the case of a charged, micron-size pure water droplet. It was demonstrated that the surface charge effectively increases surface tension leading to a reduced evaporation rate.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown by Nielsen et al (2011) that in certain cases, the influence of charge can have an appreciable effect on both the evaporation rate and the equilibrium state of a droplet. In order to determine the effects of the charge on droplet evaporation, we conducted measurements using the lowest concentration (which reaches the smallest size) of glycerol and a range of induction voltages spanning 400-800 V ( Figure 11).…”
Section: Model Treatmentmentioning
confidence: 99%
“…We have considered the influence of droplet charge on evaporation rates in previous work, 32 showing it to have negligible impact at the imbalance of positive and negative ions induced in the droplets studied in these experiments. 44 The mass transfer enhancement resulting from the flowing gas surrounding the droplet is accounted for by the inclusion of a Sherwood number (Sh) scaling of the mass flux. 33,43 The thermophysical parameters that appear in the mass flux treatment and their uncertainties have been thoroughly discussed in previous publications.…”
Section: Methodsmentioning
confidence: 99%